Powered by www.myengg.

com

5. BINOMIAL THEOREM
PREVIOUS EMACET BITS
1.

The coefficient of x24 in the expansion of (1 + x 2 )

12

1)

12

C6

2)

12

C6 + 2

12

3)

(1 + x )(1 + x )
12

C6 + 4

24

4)

[EAMCET 2009]
12

C6 + 6

Ans: 2
Sol:

(1 + x ) (1 + x
2 12

12

+ x 24 + x 36 )

= ⎡⎣ 12 C0 +12 C1x 2 +12 C 2 x 4 + ...... +12 C12 x 24 ⎤⎦ (1 + x12 + x 24 + x 36 )
Coefficient of x24 is
2.

12

C0 +12 C6 +12 C12 =12 C6 + 2

If x is numerically so small so that x2 and higher powers of x can be neglected, then

⎛ 2x ⎞
⎜1 +

3 ⎠

1)

3/ 2

( 32 + 5x )

32 + 31x
64

−1/ 5

is approximately equal to

2)

31 + 32x
64

31 − 32x
64

3)

[EAMCET 2009]

4)

1 − 2x
64

Ans: 1
⎡ 3 ⎛ 2x ⎞ ⎤ ⎡ ⎛ 5x ⎞ ⎤
Sol: ⎢1 + ⎜ ⎟ ⎥ ⎢32 ⎜ 1 + ⎟ ⎥
⎣ 2 ⎝ 3 ⎠ ⎦ ⎣ ⎝ 32 ⎠ ⎦
= [1 + x ] ( 32 )

=

−1/ 5

⎛ 5x ⎞
⎜1 + ⎟
⎝ 32 ⎠

−1/ 5

−1/ 5

1
1 5x
1
x
(1 + x ) ⎡⎢1 − × ⎤⎥ = (1 + x ) ⎛⎜1 − ⎞⎟
2
⎝ 32 ⎠
⎣ 5 32 ⎦ 2

1⎛
x ⎞ 32 + 31x
= ⎜1 + x − ⎟ =
2⎝
32 ⎠
64
3.

If (1 + x + x 2 + x 3 ) = ∑ a k x k then
5

15

k =0

1) 128

7

∑a
k =0

2k

2) 256

= .....
3) 512

Ans: 3
Sol: a 0 + a1x + a 2 x 2 + ...... + a15 x15 = (1 + x + x 2 + x 3 )

5

Put x = 1

a 0 + a1 + a 2 + ...... + a15 = 415 ………..(1)
Put x = – 1

a 0 − a1 + a 2 − ...... − a15 = 0 …………(2)

Powered by www.myengg.com

[EAMCET 2008]
4) 1024

Powered by www.myengg.com

Binomial Theorem
(1) + (2)
2 ( a 0 + a 2 + a 4 + ...... + a14 ) = 45

∴ a 0 + a 2 + a 4 + ...... + a14 = 512
4.

If a =

5
5.7 5.7.9
+
+
+ ....then a 2 + 4a =
2!3 3!32 4!33

1) 21

2) 23

[EAMCET 2008]
3) 25

4) 27

Ans: 2
Sol: a =

3.5 3.5.7
+
+ ......
2!.32 3!.33

3 3.5 3.5.7
2 + a = 1+ +
+
+ .... this one comparing with
3 3.6 3.6.9

(1 + x )

n

nx = 1,

= 1 + nx +

n ( n − 1) 2
x + ....
2!

nx ( nx − x ) 3.5
=
2
3.6

1(1 − x ) 3.5
−2
5
=
⇒ 1− x − ⇒ x =
2
3.6
3
3
3
⎛ 2⎞
nx = 1 ⇒ n ⎜ − ⎟ = 1 ⇒ n = −
2
⎝ 3⎠
n
⎛ 2⎞
∴ 2 + a = (1 + x ) = ⎜1 − ⎟
⎝ 3⎠

−3/ 2

⎛1⎞
⇒⎜ ⎟
⎝3⎠

−3/ 2

2 + a = 33/ 2 ⇒ ( 2 + a ) = 33 ⇒ a 2 + 4a = 23
2

5.

If ak is the coefficient of xK in the expansion of (1 + x + x 2 ) for k = 0, 1, 2, ……2n, then
n

a1 + 2a 2 + 3a 3 + ...... + 2na 2n is equal to
1) −a 0

[EAMCET 2007]

3) n.3n +1

2) 3n

4) n.3n

Ans: 4
Sol: We have (1 + x + x 2 ) = a 0 + a1x + a 2 x 2 + a 3 x 3 + ....a 2n x 2n on differentiating both sides, we get
n

n (1 + x + x 2 )

n −1

(1 + 2x ) = a1 + 2a 2 x + 3a 3 x 2 + ...... + 2na 2n x 2n −1

Put x = 1

a1 + 2a 2 + 3a 3 + ........... + 2na 2n = n.3n
6.

The sum of the series

3
3.5
3.5.7
....... =

+
4.8 4.8.12 4.8.12.16

2

Powered by www.myengg.com

[EAMCET 2007]

Powered by www.myengg.com

Binomial Theorem
1)

3 3

2 4

2)

2 3

3 4

3 1

2 4

3)

4)

2 1

3 4

Ans: 2
Sol:

3
3.5
3.5.7
3 3

+
....... + −
4.8 4.8.12 4.8.12.16
4 4

=

3 3
3.5
3
+

+ ..... −
4 4.8 4.8.12
4

1 1.3
1.3.5
3
= 1− +

+ ..... −
4 2.4.4 4.4.2.4.3
4
2

⎤ 3
⎛ 1 ⎞ 1(1 + 2 ) ⎛ 1 ⎞
= ⎢1 + 1⎜ − ⎟ +


⎟ + .....⎥ −
2! ⎝ 4 ⎠
⎝ 4⎠
⎢⎣
⎥⎦ 4

⎛ 1⎞
= ⎜1 − ⎟
⎝ 4⎠
7.

−1/ 2

3
2 3
=

4
3 4

2 2.5 2.5.8
1+ +
+
+ .... is equal to
4 4.8 4.8.12
1) 4−2 / 3

[EAMCET 2006]

2) 3 16

3)

3

4

4) 43/ 2

Ans: 2
2 2.5
Sol: Let s = 1 + +
+ .... on comparing with
4 4.8

(1 + x )

n

= 1 + nx +

n ( n − 1) 2
x + .....
2

2 nx ( nx − x ) 2.5
We get , nx = ,
=
4
2
4.8
2⎛2

⎜ − x ⎟ 2.5
−3
4 4
⎠=
= ⎝
⇒x=
2
4.8
4

2
⎛ 3⎞ 2
n⎜− ⎟ = ⇒ n = −
3
⎝ 4⎠ 4
n
⎛ 3⎞
∴ s = (1 + x ) = ⎜1 − ⎟
⎝ 4⎠

8.

−2 / 3

⎛1⎞
=⎜ ⎟
⎝4⎠

−2 / 3

= 3 16

The correct matching of List- I from List – II is
List – I
A) (1 − x )

[EAMCET 2006]

List – II
−n

(i)

x
x +1

3

Powered by www.myengg.com

Powered by www.myengg.com

Binomial Theorem
B) (1 + x )

−n

(ii) 1 − nx +

C) If x > 1 then 1 +

1 1
+ + ..... is
x x2

(iv)
(v)

(vi)

A

B

C

D

1)

i

iii

iv

v

3)

iii

ii

iv

v

n ( n + 1) 2
x + .......if x < 1
2!

(iii) 1 + nx +

2
3
4
+ 4 − 6 + .... is
2
x
x
x

D) If x > 1 then 1 −

n ( n + 1) 2
x .......if x < 1
2!

x
x −1

(x

x4
2

(x

+ 1)

2

x4
2

− 1)

2

A

B

C

D

2)

ii

iii

iv

v

4)

ii

iii

i

v

Ans:
Sol: We know that (i) (1 − x )
(ii) (1 + x )

9.

−n

= 1 − nx +

−n

= 1 + nx +

n ( n + 1) 2
x + ....if x < 1
2!

n ( n − 1) 2
x + ....if x < 1
2!

(iii) 1 +

1 1
1
x
+ 2 + ......... =
=
1
x x
x −1
1−
x

(iv) 1 −

2
3
x4
+
.................
=
2
x2 x4
( x 2 + 1)

If (1 + x ) = a 0 + a1x + ..... + a15 x15 , then
15

1) 110

2) 115

15

∑r a
r =1

ar
is equal to
r −1

3) 120

Ans: 3
15

Sol:

∑ r.
r =1

15
n − ( r − 1)
ar
= ∑ r.
a r −1 r =1
r

15

15

r =1

r =1

= ∑ ⎡⎣( n + 1) − r ⎤⎦ = ∑ (16 − r )
=15 + 14 + …….+ 1
=

15 ×16
= 120
2

4

Powered by www.myengg.com

[EAMCET 2005]

4) 135

Powered by www.myengg.com

Binomial Theorem
10.

If x <

1
1 + 2x
, is
, then the coefficient of x ′ in the expansion of
2
2
(1 − 2x )
2) ( 2r − 1) 2r

1) r2r

3) r22r +1

4)

[EAMCET 2005]

( 2r + 1) 2r

Ans: 4
Sol:

1 + 2x
−2
= (1 + 2x )(1 − 2x )
2
(1 − 2x )
r
⎡ 2
2.3.4.... ( r + 1)( 2x ) ⎤
2.3
2.3.....r
2
r −1
= (1 + 2x ) ⎢1 + ( 2x ) +

( 2x ) + .... +
( 2x ) +
2!
r!
( r − 1)!
⎢⎣ 1!
⎥⎦

The coefficient of xr = 2

( r + 1)! 2r
r!
.2r −1 +
r!
( r − 1)!

= r.2r + ( r + 1) .2r = 2r ( 2r + 1)
11.

The coefficient of x 3 y 4 z5 in the expansion of ( xy + yz + zx ) is
6

1) 70

2) 60

[EAMCET 2005]

3) 50

4) none of these

Ans: 2
Sol: If the general term in the above expansion contains x3y4z5 then r + t = 3, r + s = 4 and s + t = 5
Also, r + s + t = 6
Solving these equation, we get r = 1, s = 3, t = 2
Coefficient x 3 y 4 z5 =
12.

6!
= 60
1!3!2!
[EAMCET 2004]

The binomial coefficients which are in decreasing order are
1)

15

15

15

C5 , C 6 , C 7

2)

15

15

15

C10 , C9 , C8

3)

15

15

15

4)

C 6 , C 7 , C8

15

15

C7 , C6 ,15 C5

Ans: 4
Sol: The series of binomial coefficient is
15

C0 ,15 C1 ,15 C2 ,.......15 C7 ,
decrea sin g value

15

C8 ,15 C9 ........ 15 C14 ,15 C15

greatest value

decrea sin g value

From the above discussion, we can say that decreasing series is

15

C7 ,15 C6 ,15 C5

∴ Option (4) is correct
13.

If the coefficient (2r + 1)th term and (r + 2)th term in the expansion of (1 + x)42 are equal, then r is
[EAMCET 2003]
equal to :
1) 12

2) 14

3) 16

4) 18

Ans: 2
Sol: Given that coefficient of (2r + 1)th term = coefficient of (r + 2)th term
43

C2r = 43 C r +1 ⇒ 43 = 2r + ( r + 1) (or) 2r = r + 1
5

Powered by www.myengg.com

Powered by www.myengg.com

Binomial Theorem
⇒ r = 14 ( or ) r = 1

Thus r = 14
14.

The coefficient of x5 in the expansion of (1 + x 2 ) (1 + x ) is
5

1) 60

2) 50

4

3) 40

[EAMCET 2003]
4) 56

Ans : 1
5
5
4
Sol: We have (1 + x 2 ) (1 + x ) = ⎡⎢1 + 5 C1x 2 + 5 C2 x 4 + ..... + ( x 2 ) ⎤⎥

⎡⎣1 + 4 C1x + 4 C2 x 2 + 4 C3 x 3 + x 4 ⎤⎦
Coefficient to x5

=5 C1.4 C3 + 5 C2 .4 C1 = 20 + 40 = 60
5

15.

k⎞

If the coefficient of x in the expansion of ⎜ x 2 + ⎟ is 270 then k is equal to
x⎠

1) 1

2) 2

3) 3

[EAMCET 2002]

4) 4

Ans: 3
5

k⎞

Sol: General term in the expansion of ⎜ x 2 + ⎟ is
x⎠

Tr +1 = C r ( x
5

)

2 5− r

r

⎛k⎞ 5
r 10 − 3r
⎜ ⎟ = Cr k x
⎝x⎠

Let this term contains x then 10 − 3r = 1 ⇒ r = 2 then
Coefficient x =5 C3k 3 = 10k 3

10k 3 = 270
k 3 = 27 ∴ k = 3
16.

The sum of the coefficients in the expansion of (1 + x + x 2 ) is
n

2) 2n

1) 2

3) 3n

[EAMCET 2002]
4) 4n

Ans: 3
Sol: we have (1 + x + x 2 ) , put x = 1
n

= (1 + 1 + 1) = 3n
n

17.

In the expansion of (1+ x)n the coefficients of pth and (p +1)th terms are respectively p and q, then
p + q is equal to
[EAMCET 2002]
1) n

2) n + 1

3) n + 2

Ans: 2
Sol: TP = n C p −1 = P
6

Powered by www.myengg.com

4) n + 3

Powered by www.myengg.com

Binomial Theorem
TP +1 = n C p = q
n
C
p
p
p
⇒ p + q = n +1
∴ = n p −1 ⇒ =
q n − p +1
q
Cp

18.

1 1.3 1.3.5
1+ +
+
+ ....... =
4 4.8 4.8.12
1)

2)

2

[EAMCET 2001]

1
2

3)

4)

3

1
3

Ans: 1
Sol: This one comparing with (1 + x ) = 1 + nx +
n

n ( n − 1) 2
x + .....
2!

1 n ( n − 1) 2 1.3
nx = ,
x =
4
2!
4.8
1⎛1

⎜ − x ⎟ 1.3
nx ( nx − x ) 1.3
4 4
⎠=
=
⇒ ⎝
2
4.8
2
4.8

1
3
1
1
− x = ⇒ x = − = nx =
4
4
2
4

1
⎛ 1⎞ 1
n⎜− ⎟ = ⇒ n = −
2
⎝ 2⎠ 4
1 1.3
⎛ 1⎞
1+ +
+ .... = ⎜1 − ⎟
4 4.8
⎝ 2⎠
19.

−1/ 2

= 2

The coefficient of x4 in the expansion of
1) 1

(1 − 3x )
1 − 2x

2) 2

2

[EAMCET 2001]

is equal to

3) 3

4) 4

Ans: 4
Sol: we have

(1 − 3x )
1 − 2x

2

= (1 + 9x 2 − 6x ) (1 − 2x )

−1

2
3
4
= (1 + 9x 2 − 6x ) ⎡1 + 2x + ( 2x ) + ( 2x ) + ( 2x ) + .....⎤

Coefficient of x 4 = 16 + 9 ( 4 ) − 6 ( 8 ) = 4
20.

If (1 + x ) = C0 + C1x + C 2 x 2 + ...... + Cn x n then C0 + 2C1 + 3C2 + ...... + ( n + 1) Cn is equal to
n

[EAMCET 2001]
1) 2n + n.2n −1

2) 2n −1 + n.2n

3) 2n + ( n + 1) 2n

Ans:1

7

Powered by www.myengg.com

4) 2n −1 + ( n − 1) 2n

Powered by www.myengg.com

Binomial Theorem
⎛ n +1+1⎞ n
n −1
Sol: ⎜
⎟ .2 = ( n + 2 ) .2
2

= n.2n −1 + 2n (or)
Let S = C0 + 2C1 + 3C 2 + ....... + (n + 1)C n …………..(1)
S = Cn + 2Cn −1 + 3Cn − 2 + ....... + (n + 1)C0
S =(

n +1)

C0 + n C1 + ....... + Cn ………………(2)

(1) + (2)

⇒ 2S = C0 (1 + n + 1) + C1 ( 2 + n ) + ...... + Cn ( n + 1 + 1)
2S = ( n + 2 )( C0 + C1 + C2 + .... + Cn ) = ( n + 2 ) .2n

S = ( n + 2 ) .2n −1 = n.2n −1 + 2n
21.

If C0 , C1 , C 2 ,...... are binomial coefficient, then C1 + C2 + C3 + ...... + Cr + ..... + Cn is equal to
[EAMCET 2000]
2) 2n −1

1) 2n

3) 2n − 1

4) 22n

Ans: 3
Sol: we have (1 + x ) = 1 + n C1x + n C 2 x 2 + .....n Cn x n
n

Put x = 1
1 + n C1 + n C2 + ..... + n Cn = 2n
C1 + C2 + ..... + Cn = 2n − 1
22.

⎛ 1⎞
in (1 + x ) ⎜1 + ⎟
⎝ x⎠

n

n

The coefficient of x

–n

1) 0

2) 1

[EAMCET 2000]
3)2n

4)

Ans: 2

⎛ 1 ⎞ (1 + x )
Sol: (1 + x ) ⎜1 + ⎟ =
xn
⎝ x⎠

2n

n

= x − n ⎡⎣ 2n C0 + 2n C1x + ... + 2n Cn x 2n ⎤⎦
Coefficient of x − n = 2n C0 = 1
23.

If the coefficient of rth term and (2+1)th term in the expansion of (1+x)3n are in the ratio 1 : 2 the r
is equal to
[EAMCET 2000]
1)

6
( n + 1)
5

2)

1
( 3n + 1)
3

3)

1
( n + 2)
4

Ans: 2
Sol: coefficient of rth term = Tr =

3n

Cr −1
8

Powered by www.myengg.com

4)

1
( 3n + 2 )
3

Powered by www.myengg.com

Binomial Theorem
Coefficient of (r+1)th term = Tr+1 =
Given

Tr
1
= ⇒
Tr +1 2

3n

3n

Cr

Cr −1 1
r
1
1
= ⇒
= ⇒ r = ( 3n + 1)
3
Cr
2
3n − r + 1 2

3n

9

Powered by www.myengg.com